Development of the Russian Media Market and Digital Divide - E. Yu. Kolobova (Управленческое консультирование, 2019)
The influence of digitalization on the media market leads to the emergence of a new information space, but it creates a threat of a digital divide, which not only deepens information inequality, but also leads to complex socio-economic differentiation of individuals. In the institutions of the information society, the media business is divided into traditional and digital segments, where new consumer groups are formed, with access to Internet technologies, preferring active media consumption methods, capable of creating multimedia works through co-creation. The development of the media market leads to an increase in the number of media platforms with a wide range of content, as well as gradually introducing the rules of the advertising market into the system of consumption of intellectual property. If there are significant competitive advantages of interactive and digital media over traditional media, problems arise not only in the monetization of intellectual work, but also in the process of regulating competition between subjects of international journalism, including those caused by increased competition with media resources prevailing on the Internet. In the context of global changes in the media market, social inequality is increasing under the influence of Internet technologies, and the threat of economic discrimination for mass audience members arises.